Computed tomographic morphometric analysis of sacroiliac region for ventral plating of sacroiliac joint in Malay ethnicity - Singh, Sarbdev (2020)
Introduction Unstable sacroiliac joint injury treated with open reduction and internal fixation, and ventral sacroiliac joint plating has shown promising results and outcome with such injuries. The morphology of sacroiliac region however, has not been thoroughly studied in order to guide the application of screws when plating the sacroiliac joint. Hence, we performed a CT morphometric study of the sacroiliac region to determine the ideal screw trajectory and length in order to safely apply a ventral sacroiliac plate. Materials and methods A total of 112 Pelvic CT images performed in the year 2017 were measured after sagittal tilt, coronal tilt and axial rotation were adjusted. We measured sacroiliac joint angles on both true axial and coronal planes, along with osseus thickness between sacroiliac joint and 1st sacral foramina, vertical distance from superior sacral wall till mid level of 1st sacral foramina and till mid level of 2nd sacral foramina respectively. All parameters were measured up to 0.1o and 0.1mm, and statistical analysis was performed using IBM SPSS Statistics Version 24. Independent t-test was used to determine the mean difference between sacroiliac joint angles in axial and coronal plane by gender. Descriptive analysis of the numerical variable was presented as mean (standard deviation). Results The mean sacroiliac joint angle in axial plane was 13.39o (SD 5.51), sacroiliac joint angle in coronal plane was 14.17o (SD 3.43), mean osseous thickness between sacroiliac joint and 1st sacral foramina was 20.80mm (SD 3.29), mean vertical distance from superior sacral wall till 1st sacral foramina 18.67mm (SD 5.01) and till 2nd sacral foramina 42.69mm (SD 5.31) respectively. Males however showed statistically significant higher SIJ angle in coronal plane when compared to their female counterparts with p=0.02. Conclusion Ventral sacroiliac joint plating would be best when done with the screw over the sacral side inserted at an angle in the coronal plane of about 14 degrees medially, with screw length of about 37mm, and with the screw hole of the plate not exceeding 2cm medially from the sacroiliac joint, to minimise injury to the neural elements and to get best bony purchase.